Intrauterine environment and cognitive development in young twins. (28th June 2013) - Antoniou, E. E.; Fowler, T.; Thiery, E.; Southwood, T. R.; van Gestel, S.; Jacobs, N.; Vlietinck, R.; van Os, J.; Rijsdijk, F. V.; Derom, C.; Zeegers, M. P.
Abstract : Intrauterine factors important for cognitive development, such as birth weight, chorionicity and umbilical cord characteristics were investigated. A total of 663 twin pairs completed the Wechsler Intelligence Scale for Children-Revised and scores were available for Performance, Verbal and Total Intelligence Quotient (IQ). The intrauterine factors examined were birth weight, placental weight and morphology, cord knots, cord length and cord insertion. IQ scores for the varying levels of the intrauterine markers adjusting for gender and gestational age were calculated. The heritability of IQ and the association between IQ and intrauterine environment were examined. Twins with lower birth weight and cord knots had lower IQ scores. The aetiology of IQ is largely distinct from that of birth weight and cord knots, and non-shared environment may influence the observed relationships.